Therapeutic potentials of medicinal plants traditionally used during postpartum period and their molecular targets - Jain, Neelam; Sharma, Varsha; Ramawat, Kishan G (Journal of Ecobiotechnology, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Childbirth is a critical period of life and behavior towards childbirth varies from culture to culture. In many Southeast Asian cultures, postpartum period is considered important from point of view of recovery by offering a period of confinement. This study aimed to describe the plants used in diet therapy after childbirth in postpartum period, their importance and tried to assess the potential effects of the practices on the health of new mother and baby. The study shows that medicinal plants play a significant role in the recovery of new mother as they possess many biological properties and their molecular targets cover vast area. Therefore, the above mentioned plant species should be further explored for their other pharmacological characteristics for human welfare. Formulations can be prepared using these plants for the better healthcare of women.